How Neural Dynamics Shape Thought Dimensions - Hua, Jingyu (Université d'Ottawa / University of Ottawa, 2026)
Background: Spontaneous thought, particularly exemplified by mind-wandering, is characterized by a complex and multidimensional structure. This structure spans several dimensions: (1) task-relatedness (on-task vs. off-task), (2) thought content quantity (single vs. multiple), (3) thought orientation (externally vs. internally oriented), and (4) deliberate control (deliberate vs. spontaneous). While previous research has investigated these dimensions individually, a comprehensive neurodynamic framework integrating their cognitive and neural mechanisms remains lacking. Aims and Hypotheses: This thesis aims to examine the neural underpinnings of spontaneous thought through cognitive testing and electroencephalography (EEG), identifying distinct neural markers for each dimension and exploring their interrelationships. It is hypothesized that: 1. Alpha and theta oscillations will track task-relatedness and thought content quantity, 2. Task-relatedness and thought orientation will be distinguishable through neural and behavioral timescales, with task-relatedness operating on a shorter timescale than thought orientation. 3. Task-relatedness and deliberate control are tightly linked, with on-task thoughts typically being deliberate and off-task thoughts being spontaneous. Pre-stimulus neural oscillatory phase measures will predict post-stimulus task-related behaviors. Methods: Three EEG studies were conducted to examine these hypotheses. Study 1 analyzed the relationship between task-relatedness and thought content quantity using EEG measures of alpha and theta peak frequency sliding. Study 2 investigated task-relatedness and thought orientation by comparing their neural and behavioral timescales. Study 3 explored the interaction between task-relatedness and deliberate control, using phase-based neural markers such as peak frequency sliding, sample entropy, and inter-trial phase coherence. Results: Study 1 revealed that alpha and theta FS tracked task-relatedness and thought content quantity, with increased alpha FS associated with on-task, single-content thoughts and increased theta FS with off-task, multiple-content thoughts. Study 2 found that task-relatedness operates on a shorter timescale than thought orientation at both neural and behavioral levels. Study 3 demonstrated a strong link between task-relatedness and deliberate control, where on-task thoughts were typically deliberate and off-task thoughts were spontaneous. Furthermore, pre-stimulus neural oscillatory phase measures predicted post-stimulus task-related behaviors. Conclusion: These findings provide empirical support for the multidimensional nature of spontaneous thought and highlight distinct neural markers for each dimension. By integrating cognitive and neurophysiological evidence, this thesis establishes a neurodynamic framework for spontaneous thought, offering novel insights into the study of thought.
Keywords: thought dynamics; neural dynamics; spontaneous thought; mind wandering